Syntactic Formats for Free: An Abstract Approach to Process Equivalence - Klin, Bartek; Sobocinski, Pawel (BRICS Report Series, 2003)
A framework of Plotkin and Turis, originally aimed at providing an abstract notion of bisimulation, is modified to cover other operational equivalences and preorders. Combined with bialgebraic methods, it yields a technique for deriving syntactic formats for transition system specifications, which guarantee operational preorders to be precongruences. The technique is applied to the trace prorder, the completed trace preorder and the failures preorder. In the latter two cases, new syntactic formats guaranteeing precongruence properties are introduced.